Women Writers and the Images of Women Representation in the Post-Colonial Literature. Case Study of Zuwaira Isa Jos and Her Struggles. - Ibrahim, Balbasatu (Advances in Social Sciences Research Journal, 2020)
Women in Northern Nigeria although seemed and portrayed by many as naïve and back ward educationally, economically and politically, are blessed with talents and determination . These qualities make them able to struggle and overcome most of the cultural inhibitions; of gender discriminations and religious misconceptions that hinder them from participating in decision making and accessing other basic necessities for human development. They manage to break the silence and raise their voices through oral and written literature, where they lament and admonish the society against some cultural practices that are usually targeted at women folks. In this paper one of such women writers; Zuwaira Isa Jos, and her works are discussed.